The Effectiveness of Applying Electronic Learning on EFL Students’ Performance during Covid-19 Pandemic: Teachers’ Perceptions (مجلة ديالى للبحوث الانسانية, 2025)
The aim of this study is to ascertain the efficiency of Electronic learning in view of Covid-19 pandemic from the viewpoints of instructors in the Department of English at Imam Al-Kadhum University College in the subject of testing. In order to obtain the aims of the study, a descriptive analytical method was employed by the researcher. The study sample consists of 50 teachers used electronic learning system. The findings of the study were discovered that the achievement of the study sample of assessment was average. In addition, the study also deals with teachers’ assessment of the fields of electronic learning continuity, obstacles to using electronic learning, faculty interaction with electronic learning, as well as students' interactions with it as a medium of instruction. The researcher suggested organizing electronic learning training sessions for both professors and students to help remove all barriers that stem from the electronic learning system in place, as well as the necessity to merge face-to-face and e-education in higher education institutions in the future.